Three-dimensional Vascularized β-cell Spheroid Tissue Derived From Human Induced Pluripotent Stem Cells for Subcutaneous Islet Transplantation in a Mouse Model of Type 1 Diabetes. Issue 1 (January 2022) - Takaichi, Shohei; Tomimaru, Yoshito; Akagi, Takami; Kobayashi, Shogo; Fukuda, Yasunari; Toya, Keisuke; Asaoka, Tadafumi; Iwagami, Yoshifumi; Yamada, Daisaku; Akita, Hirofumi; Noda, Takehiro; Gotoh, Kunihito; et al.
Abstract : Background: Islet transplantation is an effective replacement therapy for type 1 diabetes (T1D) patients. However, shortage of donor organ for allograft is obstacle for further development of the treatment. Subcutaneous transplantation with stem cell-derived β-cells might overcome this, but poor vascularity in the site is burden for success in the transplantation. We investigated the effect of subcutaneous transplantation of vascularized β-cell spheroid tissue constructed 3-dimensionally using a layer-by-layer (LbL) cell-coating technique in a T1D model mouse. Methods: We used MIN6 cells to determine optimal conditions for the coculture of β-cell spheroids, normal human dermal fibroblasts, and human umbilical vein endothelial cells, and then, under those conditions, we constructed vascularized spheroid tissue using human induced pluripotent stem cell-derived β-cells (hiPS β cells). The function of insulin secretion of the vascularized hiPS β-cell spheroid tissue was evaluated in vitro. Furthermore, the function was investigated in T1D model NOD/SCID mice subcutaneously transplanted with the tissue. Results: In vitro, the vascularized hiPS β-cell spheroid tissue exhibited enhanced insulin secretion. The vascularized hiPS β-cell spheroid tissue also significantly decreased blood glucose levels in diabetic immunodeficient mice when transplanted subcutaneously. Furthermore, host mouse vessels were observed in the explanted vascularized hiPS β-cell spheroid tissue. Conclusions: Vascularized hiPS β-cell spheroid tissue decreased blood glucose levels in the diabetic mice. This therapeutic effect was suggested due to host angiogenesis in the graft. This method could lead to a promising regenerative treatment for T1D patients. Abstract : Supplemental Digital Content is available in the text.